INCREASE SERVICE SALES TURNOVER THROUGH A DIGITAL MARKETING APPROACH: EFFECTIVE? - Fauzia, Ulfa; Farida, Nur; Utomo, Priyo (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2025)
This study aims to analyze the influence of price and product innovation on purchasing decisions of gold jewelery at Toko Emas Gadjah, located in Bali . In an increasingly competitive market environment, price and product innovation are key determinants that significantly affect consumer preferences and behavior in selecting gold jewelry products. The research adopts a quantitative approach using a survey method by distributing questionnaires to 100 respondents who are active customers of Toko Emas Gadjah. The results of data analysis indicate that the price variable has a significant influence on purchasing decisions, as consumers tend to consider affordability and price competitiveness before making a purchase. Additionally, product innovation encompassing variety in design, uniqueness and novelty also contributes positively to consumer purchasing decisions. These findings offer managerial implications for store owners and managers, particularly in formulating competitive pricing strategies and encouraging the development of innovative products that align with market preferences, with the aim of enhancing product attractiveness and increasing sales volume. Keywords: Price, Product Innovation, Purchase Decision, Gold Jewellery, Gadjah Gold Shop